معوقات التنمية الاجتماعية - نصراه, واحدة حمةويس (Sulaimani Journal for Humanities, 2021)
The aim of this research is to find out the primary obstacles that stand against of social development, the research is one of analytical theoretical research that consists of five subjects: first object covers the general frame of the research and the main concepts, second subject was assigned for previous studies. Third subject consists of most important directions of social development, forth subject was assigned to explain social development, including: goals methods, necessities and types of social development, fifth and the last subject was assigned to the obstacles of social development, conclusions the research's suggestions, recommendations and propositions, the research come up with some results the most significant that :(the social development obstacles are internal to the society itself, economy, and external obstacles such as dependency, technological, political, social, psychological, with deficiency, in specialists in addition to ignorance of people who are responsible for the process of social developmen